2024
DOI: 10.3233/tub-220039
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor markers for response prediction and monitoring of advanced lung cancer: A review focusing on immunotherapy and targeted therapies

Abstract: BACKGROUND: The value of serum tumor markers (STMs) in the current therapeutic landscape of lung cancer is unclear. OBJECTIVE: This scoping review gathered evidence of the predictive, prognostic, and monitoring value of STMs for patients with advanced lung cancer receiving immunotherapy (IT) or targeted therapy (TT). METHODS: Literature searches were conducted (cut-off: May 2022) using PubMed and Cochrane CENTRAL databases. Medical professionals advised on the search strategies. RESULTS: Study heterogeneity li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies have supported the use of predictive and prognostic biomarkers to monitor response to various treatment modalities in NSCLC [25,26,[28][29][30]. A recent meta-analysis of studies analyzing the predictive and prognostic utility of CYFRA 21-1 and CEA concluded that both markers may be used for monitoring treatment response, and that biomarkers may have a role in prediction of treatment response [29,31], although no conclusions could be drawn based on patients' RECIST category. Despite the growing body of supporting evidence, the use of serum tumor markers for the monitoring of response to therapy has not yet been incorporated into current guidelines [5,14], possibly because it remains unclear how they should be used in conjunction with imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have supported the use of predictive and prognostic biomarkers to monitor response to various treatment modalities in NSCLC [25,26,[28][29][30]. A recent meta-analysis of studies analyzing the predictive and prognostic utility of CYFRA 21-1 and CEA concluded that both markers may be used for monitoring treatment response, and that biomarkers may have a role in prediction of treatment response [29,31], although no conclusions could be drawn based on patients' RECIST category. Despite the growing body of supporting evidence, the use of serum tumor markers for the monitoring of response to therapy has not yet been incorporated into current guidelines [5,14], possibly because it remains unclear how they should be used in conjunction with imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond classical chemotherapies they could become important diagnostic tools for modern therapies. This is shown in a review of van den Heuvel et al [39] on the role of serum tumor markers for response prediction and monitoring the response to immunotherapy and targeted therapies.…”
Section: Special Issue On "Lung Cancer Tumor Markers"mentioning
confidence: 99%